Philosophical Notes on Solitude in One Hundred Years of Solitude (1967) by Gabriel García Márquez - Lema-Hincapié, Andrés (2016)
The title of the novel Gabriel García Márquez publishes in 1967 has not been thought enough. I argue that the word solitude in its title should be understood as pointing out at a human truth that “touches the heart” −to use a complex metaphor by William Faulkner. I will build my arguments by referring to what I love to call “suggestive anachronisms”. Thanks so such anachronisms, I will make talk together works and authors García Márquez almost surely did not have in mind while he was writing his One Hundred Years of Solitude. I am thinking, for instance, of Michel de Montaigne, Miguel de Unamuno, and Xavier Zubiri. Notwithstanding, it is my hope that, by the means of such a procedure, new possible meanings −plausible ones− can be brought to light in relation to the concept I will be studying throughout my pages, namely, solitude.